The influence of online sales and purchases among diploma students in Puncak Alam : a study on part 1 and part 5 of ACIS students / Zafirah Ab Malek - Ab Malek, Zafirah (Universiti Teknologi MARA, Selangor, Puncak Alam Campus, 2018)
Business and purchases online is process of doing business through internet networks. Nowadays, every community has their own gadgets such as smart phone, computer, laptop, tab and many more as their important items in their life. With this technological developments, e-commerce already take place in our life and society. A person can sitting on their chair in front of their gadgets and access all the facilities of the internet to buy or sell the products. Unlike traditional commerce, it carried out physically with effort of a person to go and get products, but e-commerce has made it easier for society to reduce physical work and to save time. The main advantages why society chose this option to do business or purchases because they can only browse online shops through their gadgets without taking much time, comparing the prices and order merchandise sitting at home at their gadgets. Besides, this advancement of e-commerce also is essential for a developing country such as Malaysia.